Classification and assessment of bioclimatic conditions for tourism, health resort and someweather therapies in Vietnam - Nguyen, Khanh Van (VNU, 2014)
By using the integrated analysis and quantitative method, this paper presents the results of classification and assessment of bioclimatic conditions for tourism, health resort, and weather therapies, based on 1,826 weather combinations of 19 meteorological stations of Vietnam in the period of 2001-2005. 1. In the territory of Vietnam, the number of good weather days for tourism and human health varies in a wide range: from 308.4 days per yearin Vung Tau to 109.6 days per year in Sa Pa. For tourism, excursion, sea vacation in the lowland area: Vung Tau, Con Dao and Nha Trang have about 300 good weather days per year; Phan Thiet, Hanoi, Dong Hoi, Hue, Rach Gia have 250-280 days per year; Co To, Tay Ninh, Ho Chi Minh City,... have about 200 days per year. For health resort and some weather therapies in the highland area: Moc Chau has 207.7 days per year; Da Lat - 183.7 days per year; Tam Dao - 129 days per year; and Sa Pa - 109 days per year. 2. In Vietnam, the good weather period varies across regions: For tourism, excursion, and sea vacation in the lowland area: In the Northeast Region, the good tourism period lasts from April to the end of November. In the Northern Region, this period lasts longer, it is just interrupted in February, when the weather is damp by mild drizzle. In the Central and Southern regions, this period is not only around year, but also distributed evenly during a year. For health resort and some weather therapeutic medical treatment in the highland area: In the Northern Region, the good weather period for health resort and some weather therapies is shorter then in the South and it is concentrated mainly in the summer time. In Central Plateau such as Da Lat this period lasts around year.